Global Attractivity and Periodic Solution of a Discrete Multispecies Cooperation and Competition Predator-Prey System - Zheyan Zhou (Discrete Dynamics in Nature and Society)
We propose a discrete multispecies cooperation and competition predator-prey systems. For general nonautonomous case, sufficient conditions which ensure the permanence and the global stability of the system are obtained; for periodic case, sufficient conditions which ensure the existence of a globally stable positive periodic solution of the system are obtained.